Cost-oriented process optimisation through variation propagation management for aircraft wing spar assembly. (June 2019) - McKenna, Vincent; Jin, Yan; Murphy, Adrian; Morgan, Michael; Fu, Rao; Qin, Xuda; McClory, Caroline; Collins, Rory; Higgins, Colm
Highlights: A novel variation propagation model was developed for an overconstrained wing spar assembly. Cost models for both part fabrication and assembly processes were related to the variation model for the first time. Monte Carlo simulations were completed to investigate the variation effects on Key Characteristics and the associated costs in different scenarios. The cost variations resulting from the geometric or process variations can be easily identified, so that the manufacturing processes through the production chain can be optimised. This method will be useful for product designers to allocate suitable dimensions and tolerances, and for production planners to arrange the fabrication and assembly processes in an optimised manner. Abstract: Overconstrained assemblies such as aircraft sub-assemblies present a challenge to production planners, as variations in parts and processes can make it difficult to achieve all assembly Key Characteristics (KCs) simultaneously. Despite assigning tight tolerances to sub-component manufacture, part variation propagation necessitates expensive and time-consuming variation management processes such as shimming in order to ensure the final assembly is within specification. This paper presents for the first time a variation propagation model for overconstrained assemblies, and develops a novel modelling method to connect variations with production costs. This facilitates a novel process optimisation method based on variation propagation, with the ability to analyse the trade-offs between the cost and achievable variation limits of the entire manufacturing chain in order to minimise the overall manufacturing cost. An overconstrained wing spar assembly is used as a case study to validate the methodology.